Diagnostic and Prognostic Significance of Dysregulated Expression of Circular RNAs in Osteosarcoma. (1st February 2021) - Zhang, Chenghao; He, Jieyu; Qi, Lin; Wan, Lu; Wang, Wanchun; Tu, Chao; Li, Zhihong
ABSTRACT: Objective: This study aimed to perform an updated meta-analysis to explore the clinical, diagnostic, and prognostic values of circRNAs in osteosarcoma. Methods: : PubMed, Web of Science, EMBASE, Scopus, and Cochrane Library were systematically searched up to December 15, 2020. Eligible studies regarding the relationship between circRNAs levels and clinicopathological, diagnostic, and prognostic values in osteosarcoma were included for study. Results: 31 studies involving 1979 osteosarcoma patients were enrolled, with 22 studies on clinicopathological parameters, eleven on diagnosis, and 23 on prognosis. For clinical parameters, overexpression of oncogenic circRNAs was intimately correlated with larger tumor size, advanced Enneking stage, poor differentiation, and distant metastasis (DM). In contrast, the downregulated circRNAs showed negative correlation with Enneking stage and DM. For the diagnostic values, the summary area under the curve of circRNA for the discriminative efficacy between osteosarcoma patients and non-cancer counterparts was estimated to be 0.87, with a weighted sensitivity of 0.79, specificity of 0.81, respectively. For the prognostic significance, oncogenic circRNAs had poor overall survival (OS) and disease-free survival, while elevated expression of tumor-suppressor circRNAs were closely related to longer OS. Conclusion: This study showed that aberrantly expressed circRNA signatures could serve as potential biomarkers in diagnosis and prognosis in osteosarcoma.